Reactions of Enaminones with p-Quinone Methides: Access to 4H-Chromene and 4H-Chromen-4-one Derivatives - Singh, Gurdeep; Sharma, Sonam; Rekha; Pandey, Rajat; Singh, Rupali; Kumar, Tarunjeet; Anand, Ramasamy Vijaya (John Wiley & Sons, 2022)
A one-pot approach for the synthesis of oxygen-containing heterocycles such as 4H-chromenes and 4H-chromen-4-ones has been established through the reaction of enaminones with p-quinone methides (p-QMs). This transformation basically involves an acid-catalyzed 1,6-conjugate addition of enaminones to p-QMs followed by annulation. In the case of reaction between 2-hydroxyphenyl-substituted p-quinone methides and N,N-dimethyl enaminones, 4H-chromene derivatives were obtained in moderate to excellent yields. Similarly, the reaction between simple p-quinone methides and 2-hydroxyphenyl-substituted N,N-dimethyl enaminones led to 4H-chromen-4-one derivatives in good yields.
Only IISER Mohali authors are available in the record.
Keywords: Enaminones with p-Quinone Methides; 4H-Chromene; 4H-Chromen-4-one Derivatives